Impact of Metal and Metal Oxide Nanoparticles on Plant: A Critical Review - Rastogi, Anshu; Zivcak, Marek; Sytar, Oksana; Kalaji, Hazem M.; He, Xiaolan; Mbarki, Sonia; Brestic, Marian (Frontiers in Chemistry, 2017)
An increasing need of nanotechnology in various industries may cause a huge environment dispersion of nanoparticles in coming years. A concern about nanoparticles interaction with flora and fauna is raised due to a growing load of it in the environment. In recent years, several investigators have shown impact of nanoparticles on plant growth and its accumulation in food source. This review examines the research performed in the last decade to show how metal and metal oxide nanoparticles are influencing the plant metabolisms. We addressed here, the impact of nanoparticle on plant in relation to its size, concentration, and exposure methodology. Based on the available reports, we proposed oxidative burst as a general mechanism through which the toxic effects of nanoparticles are spread in plants. This review summarises the current understanding and the future possibilities of plant-nanoparticle research.